2009
DOI: 10.1088/0951-7715/22/12/004
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation theory for the nonlinear Schrödinger equation with a random potential

Abstract: A perturbation theory for the Nonlinear Schrödinger Equation (NLSE) in 1D on a lattice was developed. The small parameter is the strength of the nonlinearity. For this purpose secular terms were removed and a probabilistic bound on small denominators was developed. It was shown that the number of terms grows exponentially with the order. The results of the perturbation theory are compared with numerical calculations. An estimate on the remainder is obtained and it is demonstrated that the series is asymptotic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 65 publications
4
72
0
Order By: Relevance
“…The question of whether or not localization is stable in the presence of interactions was first considered by Fleishman and Anderson [4], who concluded that short-ranged interactions cannot destabilize the insulating phase. A similar and still open question also exists for Bose-Einstein condensates, treated in the framework of the time-dependent Gross-Pitaevskii (or nonlinear Schrödinger) equation [5]. In this case numerics, as well as analytical arguments, suggest a temporally sub-diffusive or even logarithmic thermalization behavior for not very strong interactions [5].…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…The question of whether or not localization is stable in the presence of interactions was first considered by Fleishman and Anderson [4], who concluded that short-ranged interactions cannot destabilize the insulating phase. A similar and still open question also exists for Bose-Einstein condensates, treated in the framework of the time-dependent Gross-Pitaevskii (or nonlinear Schrödinger) equation [5]. In this case numerics, as well as analytical arguments, suggest a temporally sub-diffusive or even logarithmic thermalization behavior for not very strong interactions [5].…”
mentioning
confidence: 92%
“…A similar and still open question also exists for Bose-Einstein condensates, treated in the framework of the time-dependent Gross-Pitaevskii (or nonlinear Schrödinger) equation [5]. In this case numerics, as well as analytical arguments, suggest a temporally sub-diffusive or even logarithmic thermalization behavior for not very strong interactions [5].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…We consider here the one-dimensional random discrete nonlinear Schrödinger (DNLS) system (see, e.g., [9][10][11][12][13][14]), iψ n = ( n + χ|ψ n | 2 )ψ n − C(ψ n+1 + ψ n−1 ),…”
mentioning
confidence: 99%
“…From a practical perspective, it can yield some insight on the nonlinear Anderson model via multi-state resonance phenomenon, [9].…”
Section: Previous Resultsmentioning
confidence: 99%